Sea-quark dynamics in decuplet ( $$\frac{3}{2}^+$$ 3 2 + ) $$→ $$ → octet ( $$\frac{1}{2}^+$$ 1 2 + ) transition quadrupole moment - Preeti Bhall; Alka Upadhyay (European Physical Journal C: Particles and Fields)
Abstract We investigated the electromagnetic quadrupole transition of baryon decuplet ( $$J^P= \frac{3}{2}^+$$ J P = 3 2 + ) to octet ( $$J^P= \frac{1}{2}^+$$ J P = 1 2 + ) using the statistical framework together with the principle of detailed balance. The statistical approach assumed the expansion of hadrons in terms of various quark–gluon Fock states. By specifying the appropriate multiplicity in spin, color and flavor space, the relative probabilities of strange and non-strange quark–gluon Fock state are calculated. These probabilities further accumulated in the form of statistical parameters, highlighting the importance of sea quarks and gluons in the electromagnetic transition. Our calculations includes the individual contribution of valence and sea (scalar, vector and tensor ) to the transition moment of baryons. The effect of flavor SU(3) symmetry and its breaking in both valence and sea quarks is studied by incorporating the strange quark mass. The strangeness in the sea is constrained by a suppression factor $$(1-C_l)^{n-1}$$ ( 1 - C l ) n - 1 , which depends upon the free energy of gluons. The computed results get affected upto 60 $$%$$ % and exhibit the dominance of octet sea. The present work has been compared with updated experimental data and various theoretical predictions. The results obtained may offer important insights for future experimental studies.